The gut-brain peptide cyclo(His-Pro) is secreted in a pulsatile fashion in fasting humans - Herminghuysen, D.; Cook, C.; Thompson, H.; Bostick, D.; Lee, F.; Stokes, L.; Hilton, C.; Prasad, C. (Neuropeptides (Edinburgh), 1994)
Histidyl-proline diketopiperazine (CHP) is a cyclic dipeptide that is found in many animal tissues, most notably brain and gut. It has been found to have a variety of biologic actions and has been postulated to play a role in appetitive behavior and energy metabolism. This study was conducted in order to characterize the secretory pattern of CHP during a 24 h fast. Four subjects (2 obese and 2 lean) were studied during the latter 24 h of a 36 h fast. Blood was sampled every 10–15 min and assayed for CHP concentration using a specific radioimmunoassay. Analysis revealed that circulating CHP oscillates in humans and that diurnal variation occurred but only in the obese subjects.